Pengaruh Pengetahuan Perpajakan, Sanksi Perpajakan Dan Pemahaman Perpajakan Terhadap Wajib Pajak Umkm Setelah Diterbitkan Uu Harmonisasi No. 7 Tahun 2021 (Studi Kasus pada Dinas Koperasi, Usaha Mikro dan Tenaga Kerja Kota Kediri) - Yolla Norma Miracel; Eny Srihastuti; Agus Athori (JURNAL AKUNTANSI DAN MANAJEMEN MUTIARA MADANI, 2022)
This research sought to determine the impact of tax knowledge, tax sanctions, and understanding of taxation toward taxpayers compliance on MSMEs after published of harmonization law number 7 year of 2021. The government stipulates a tax rate of 0.5% but on condition that the gross turnover in a year is less than Rp500 million, which is exempt from tax payments. So, MSME actors are only subject to tax if the turnover in one year is more than Rp500 million. Using the slovin formula and random sampling, this study had 100 participants. The data analysis techniques used multiple linear regression, and t test. The research found that knowledge of taxation and tax sanctions had no substantial impact on MSMEs taxpayer compliance. Meanwhile, the understanding variable has a substantial impact. The result of the determinant coefficient calculation is 0.293, which indicates that only 29.3% of taxpayer compliance is influenced by tax knowledge, tax sanctions, and tax understanding, with the other 70.7% being influenced by other variables not examined in this study.